Tindak Tutur Ekspresif dalam Novel Bumi Manusia karya Pramoedya Ananta Toer - Nursiah Nursiah; Siti Ainim Liusti (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2020)
This study aims to describe the types of expressive speech acts and strategy used in the novel Bumi Manusia by Pramoedya Ananta Toer. This type of research is qualitative research using descriptive methods. The data contained in this study are words, phrases, clauses, and sentences that refer to expressive speech acts contained in the novel Bumi Manusia by Pramoedya Ananta Toer. The data source of this research is the novel Bumi Manusia by Pramoedya Ananta Toer. The research instrument is the researcher himself with a note taking tool to record things that indicate expessive speech acts found in the novel . Data collection techniques were carried out in several stages including reading and understanding the novel Bumi Manusia by Pramoedya Ananta Toer; (2) identifying data containing expressive speech acts in the novel Bumi Manusia by Pramoedya Ananta Toer; and (3) inventorizing data containing expressive speech acts in the novel Bumi Manusia by Pramoedya Ananta Toer. The data validation technique used in this study is a detailed description technique. The data analysis technique is done by classifying the data, analyzing the data, and concluding the results of the research. The research results found, namely (1) types of expressive speech acts in the novel Bumi Manusia by Pramoedya Ananta Toer in the from of saying thanks, saying congratulations, apologizing, praising, accusing, exressing anger, expressing pleasure, feeling embarrased, and feeling surprised; (2) the storytelling strategy used by the characters Minke, Annalies, dan Nyai Ontosoroh is in the form of a stratedy without the nonsense, a strategy of a speaking with pleasantries of positive courtesy, a strategy of speaking with small talk of negative politeness, vague speech strategies, and strategies that speak silently